PENERAPAN METODE COACHING DALAM PEMBELAJARAN PENDIDIKAN AGAMA KATOLIK UNTUK MENINGKATKAN KEMANDIRIAN BELAJAR PADA SISWA KELAS VII SMP NEGERI SATAP NONOTBATAN TAHUN AJARAN 2023/2024 - Kolo, Anna Bertha; Yata Mones, Anselmus; Cornelis Usboko, Wilibrordus (JURNAL PROPHETA, 2025)
The research focus of this paper is the method taken to increase the learning independence of Class VII students at SATAP Nonotbatan State Middle School by using the coaching learning method. The steps of this method are coaching presence, active listening, powerful questions, giving feedback. The aims of this research are (1) to increase the learning independence of Class VII students at SATAP Nonotbatan State Middle School; (2) To determine the effectiveness of implementing the coaching method of learning on the material "Jesus is Merciful" for Class VII students at SATAP Nonotbatan State Middle School. The subjects of this research were Class VII students at SATAP Nonotbatan State Middle School for the 2023/2024 academic year. The type of research used is Classroom Action Research. This research was carried out in three cycles, starting with planning, then implementation, observation and ending with reflection which was carried out in one meeting. The results of the research show that the application of the coaching method can increase the learning independence of Class VII students in Catholic religious education learning, where in cycle I it was 43.66% with poor criteria, cycle II increased to 79.77% with good criteria and cycle III increased to 97.44% with very good criteria. Based on the results of this research, the researcher concluded that the coaching method could increase the learning independence of class VII students at SATAP Nonotbatan State Middle School for the 2023/2024 academic year, seen from observations that occurred during III, namely that the students' attitudes met the criteria for learning independence.